Out of sight, out of mind : homeless children and families in small-town America - Vissing, Yvonne Marie (The University Press of Kentucky, 1996)
""Homelessness in small towns and rural areas is on the rise. Drawing on interviews with and case studies of three hundred children and their families, with supporting statistics from federal, state, and private agencies, Vissing illustrates the impact this social problem has upon education, health, and the economy.""